2009
DOI: 10.4067/s0718-16202009000300002
|View full text |Cite
|
Sign up to set email alerts
|

Phytostabilization of massive mine wastes with native phytogenetic resources: potential for sustainable use and conservation of the native flora in north-central Chile

Abstract: has left an important legacy of inadequately abandoned tailing storage facilities (TSFs) in the north-central area of Chile, and they may pose environmental risks. The Chilean government has recently established new regulations governing the closure of TSFs, and these regulations favor the use of environmentally sustainable technologies. Among these technologies is phytostabilization, which can use native plant species that may also have economic and/or subsistence value. Phytostabilization programs based on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Phytostabilization studies of metal contaminated soils are highly documented from Europe, Northern America and from Australia (Winterhalder, 1996;Kiikkilä, 2003;Li, 2006;Vangronsveld et al, 2009;Orchard et al, 2009). In contrast, little studies and projects on the phytostabilisation of contaminated soils by heavy metals are performed in tropical Africa.…”
Section: Introductionmentioning
confidence: 98%
“…Phytostabilization studies of metal contaminated soils are highly documented from Europe, Northern America and from Australia (Winterhalder, 1996;Kiikkilä, 2003;Li, 2006;Vangronsveld et al, 2009;Orchard et al, 2009). In contrast, little studies and projects on the phytostabilisation of contaminated soils by heavy metals are performed in tropical Africa.…”
Section: Introductionmentioning
confidence: 98%
“…Plants that spontaneously grow on mine spoils are potential sources of germplasm for phytoremediation purposes (Bech et al, 2002). In this context different mining areas have already been screened for useful plant species (Orchard et al, 2009). However little is known on the tolerance and accumulation of Sb in plants growing on polluted areas, especially in the Western Mediterranean zone.…”
Section: Introductionmentioning
confidence: 99%
“…Plants that naturally occur in anthropogenically contaminated soils are potential hyperaccumulators and can be studied for phytoremediation purposes (Bech et al, 2002). Many areas with developed mining and industrial activities have already been screened for hyperaccumulating species (Orchard et al, 2009). For example, Xue et al (2004) have found a new Mn-hyperaccumulator Phytolacca acinosa in the vicinity of manganese-ore mine, which is located in the city of Xiangtan, China.…”
Section: A Research Methodology In Prospection For New Hyperaccumulatorsmentioning
confidence: 99%